Phytochemical profiling, antioxidant, and tyrosinase inhibitory potential of the Acacia cyclops trunk bark: in vitro combined with in silico approach - Kaplan, Muammer; Beyaoui, Ahlem; Jlizi, Salma; Goren, Ahmet Ceyhan; Jalouli, Maroua; Harrath, Abdel Halim; Ben Jannet, Hichem (Wiley, 2024)
The aim of this study was to analyze the phytochemical profile of Acacia cyclops trunk bark ethyl acetate extract using LC-tandem mass spectrometry for the first time, along with evaluating its antioxidant and anti-tyrosinase properties. Consequently, we determined the total phenolic and flavonoid contents of the extract under investigation and identified and quantified 19 compounds, including phenolic acids and flavonoids. In addition to assessing their antioxidant potential against DPPH (2,2-diphenyl-1-picrylhydrazyl) and ABTS (2,2 '-azino-bis-[3-ethylbenzothiazoline-6-sulfonic] acid) assays, in vitro and in silico studies were conducted to evaluate the tyrosinase inhibitory properties of the A. cyclops extract. The ethyl acetate trunk bark extract exhibited a substantial total phenolic content and demonstrated significant antioxidant activity in terms of free radical scavenging, as well as notable tyrosinase inhibitory action (half-maximal inhibitory concentration [IC50] = 14.08 +/- 1.10 mu g/mL). The substantial anti-tyrosinase activity of the examined extract was revealed through molecular docking analysis and druglikeness prediction of the main selected compounds. The findings suggest that A. cyclops extract holds promise as a potential treatment for skin hyperpigmentation disorders.
Keywords: < fixed-case > Acacia cyclops; antioxidant; anti-tyrosinase; in silico; LC-MS/MS